Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1365-2036.2008.03787.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: zinc supplementation for acute gastroenteritis in children

Abstract: SUMMARY BackgroundUncertainty exists regarding the use of zinc in the treatment of acute gastroenteritis in children living in Europe, where zinc deficiency is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 27 publications
3
37
2
14
Order By: Relevance
“…Moreover, secretory compartments in other exocrine and endocrine cells have also been implicated as potential pools for similar levels of Zn 2ϩ sequestration and secretion (28,33). The availability of Zn 2ϩ in the lumen of the gastrointestinal tract has been implicated in infectious diarrheas of childhood (27,30) and in the regulation of activity of bacterial enterotoxins (9). Moreover, in adults, therapy with proton pump inhibitors has been implicated in infectious diarrheas, such as those caused by Clostridium difficile (12), the causes remaining unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, secretory compartments in other exocrine and endocrine cells have also been implicated as potential pools for similar levels of Zn 2ϩ sequestration and secretion (28,33). The availability of Zn 2ϩ in the lumen of the gastrointestinal tract has been implicated in infectious diarrheas of childhood (27,30) and in the regulation of activity of bacterial enterotoxins (9). Moreover, in adults, therapy with proton pump inhibitors has been implicated in infectious diarrheas, such as those caused by Clostridium difficile (12), the causes remaining unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies in India, Nigeria and Pakistan have not observed an association between malnutrition and OPV immunogenicity [110][111][112]. Similarly, supplementation with vitamin A did not significantly impact OPV seroconversion rates during trials in Bangladesh, Indonesia and Ghana [113][114][115], while the receipt of zinc supplements (which are known to have a significant therapeutic effect during the treatment of acute gastroenteritis [116]) had no effect on OPV seroconversion during a recent placebo-controlled trial in Pakistan [117].Data regarding the potential impact of malnutrition on oral vaccines other than OPV are limited [108]. During a trial of CVD 103-HgR in Bangladesh, supplementation with zinc (but not vitamin A) significantly boosted vibriocidal antibody response [118].…”
mentioning
confidence: 91%
“…Con respecto a la aceptación de los compuestos de zinc administrados por vía oral, estos se consideran seguros cuando se consumen en dosis fisiológicas, a pesar de que efectos secundarios como el sabor metálico, las náuseas y el vómito hayan sido descritos en la literatura (13,15,36,37), aunque con gran heterogeneidad entre los estudios en cuanto al tipo de compuesto de zinc suministrado, el tiempo de intervención y las dosis (37); tales efectos, sin embargo, no se han reportado como graves (20,24,38). Esto se corrobora en el presente estudio, en el cual ningún niño presentó efectos secundarios que requirieran tratamiento adjunto o la suspensión del consumo del complemento con zinc suministrado.…”
Section: Discussionunclassified
“…A pesar de su seguridad y baja toxicidad, estos compuestos pueden desencadenar efectos secundarios como náuseas, vómitos y dolor abdominal (15)(16)(17), sin mencionar su sabor desagradable, por lo que es necesario buscar vehículos que enmascaren su sabor para administrarlo a niños.…”
Section: Según El International Zinc Nutrition Consultativeunclassified